Flow‐Synthesis of Nucleosides Catalyzed by an Immobilized Purine Nucleoside Phosphorylase from Aeromonas hydrophila: Integrated Systems of Reaction Control and Product Purification. Issue 11 (10th August 2015) - Calleri, Enrica; Cattaneo, Giulia; Rabuffetti, Marco; Serra, Immacolata; Bavaro, Teodora; Massolini, Gabriella; Speranza, Giovanna; Ubiali, Daniela
Abstract A purine nucleoside phosphorylase from Aeromonas hydrophyla (AhPNP) was covalently immobilized in a pre‐packed stainless steel column containing aminopropylsilica particles via Schiff base chemistry upon glutaraldehyde activation. The resulting AhPNP‐IMER (Immobilized Enzyme Reactor, immobilization yield ≈50%) was coupled on‐line through a 6‐way switching valve to an HPLC apparatus containing an analytical or a semi‐preparative chromatographic column. The synthesis of five 6‐modified purine ribonucleosides was carried out by continuously pumping the reaction mixture through the AhPNP‐IMER until the highest conversion was reached, and then directing the reaction mixture to chromatographic separation. The conditions of the AhPNP‐catalyzed transglycosylations (2:1 ratio sugar donor:base acceptor; 10 mM phosphate buffer; pH 7.5; temperature 37 °C, flow rate 0.5 mL min−1) were optimized by a fractional factorial experimental design. Coupling the bioconversion step with the product purification in such an integrated platform resulted in a fast and efficient synthetic process (yield=52–89%; <10 mg) where sample handling was minimized. To date, AhPNP‐IMER has retained completely its activity upon 50 reactions in 10 months.